ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Yukalfin Hulu; Friska L. Situngkir (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Mathematical conceptual understanding is one of the fundamental competencies that students must possess in mathematics learning because it serves as the basis for understanding, connecting, and applying mathematical concepts to solve problems. However, many students still experience difficulties in understanding mathematical concepts, particularly in the topic of quadratic functions. This study aimed to analyze junior high school students' mathematical conceptual understanding of quadratic functions. The research employed a qualitative descriptive approach and was conducted at SMP Negeri 1 Gomo, South Nias Regency, involving 30 ninth-grade students as the research subjects. Data were collected through a mini-test consisting of four essay questions designed based on the cognitive levels of Bloom’s Taxonomy, namely application (C3), analysis (C4), evaluation (C5), and creation (C6). The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that students' mathematical conceptual understanding was still relatively low. The highest percentage of correct answers was found in the application (C3) question, reaching 40.0%, while the lowest percentage was found in the creation (C6) question, at 20.0%. The analysis of students' responses indicated that most students experienced difficulties in explaining mathematical concepts using their own words, identifying examples and non-examples of quadratic functions, applying concepts accurately in problem-solving, and relating quadratic function concepts to other mathematical concepts. The dominant errors included misconceptions about exponentiation operations, incorrect determination of the vertex and maximum or minimum values of quadratic functions, and misconceptions regarding the relationship between the discriminant and the minimum value of a quadratic function. Therefore, the teaching of quadratic functions should emphasize activities that promote conceptual understanding through exploration, multiple mathematical representations, discussion, and problem-solving, enabling students not only to master mathematical procedures but also to develop a deep understanding of mathematical concepts.